PROFIL KECEMASAN WANITA MEMASUKI MASA MENOPAUSE DI KELURAHAN LIMAU MANIS SELATAN KECAMATAN PAUH KOTA PADANG - Herman, Niki Yulita; Hasan, Marwisni; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
The problems was studied based on phenomena that researcher discovered in the field are some of women feel anxiety impend of entering menopause at southern, the researchers raised concerns about the study: profile of women entering menopause anxiety in the Village of South Limau Manis Padang Pauh sub district. Purpose of this research was to describe: 1) Profile of women entering menopause anxiety seen from the physical aspect in the southern Limau Manis district of Padang Pauh. 2) Profile of women entering menopause anxiety seen from psychological aspect in the southern Limau Manis District of Padang Pauh. This research was a descriptive study that try to describe the way thing are. The population of this study was all women aged 40-45 years who will enter menopause. It was about 40 people. Techniques to takes the sample was total sampling. The instrument used in this study was a questionnaire. while to data analysis used the percentage techniques .result of this research revealed that: 1) Profile of women entering menopause anxiety experienced of physical anxiety at high category in the southern Limau Manis Village District of Pauh Padang. 2) Profile of women entering menopause anxiety experienced of psychological anxiety at high category in the southern Limau Manis District of Padang Pauh. Based on the results of the study researcher suggest that women entering the menopause in order to increase knowledge about menopause and anxiety experienced by both physical and psychological aspects to better prepare for the arrival of menopause, the community leaders in order to provide education to the public regarding menopause in institutions such as: Assembly Taklim, health centers, to further research in order to make this research more urgency in developing discussion of women entering menopause anxiety.